Outdoor recreation in Sweden during and after the COVID-19 pandemic - management and policy implications - Hansen, Andreas Skriver; Beery, Thomas; Fredman, Peter; Wolf-Watz, Daniel (Journal of environmental planning and management, 2023)
This paper reports results from three studies concerning outdoor recreation participation and trends during the COVID-19 pandemic in Sweden. The studies, undertaken at national, regional and local levels, used surveys, interviews and PPGIS approaches, to build a solid knowledge base. Results are analyzed with particular attention given to management and policy implications based on the following observations: increased outdoor recreation participation, changes in lifestyle and routines, new visitor profiles and activity trends, spatial changes, visitor displacement, spatial redistribution, and indications of post-pandemic outdoor recreation behavior. The Swedish case is of special interest because of high accessibility to nature areas and few restrictions to recreate in nature due to the pandemic. Hence, this study could serve as a reference for other countries with more COVID-19 related restrictions and less accessible nature for recreation.